PENGUKURAN KINERJA KEUANGAN DENGAN PENDEKATAN EGONOMIC VALUE ADDED DAN FINANCIAL VALUE ADDED - Felisia . (Center for Economic Studies Universitas Katolik Parahyangan, 2011)
Performance measurement has become an important indicator not only for companies but also for investors. It indicates the capability of companies in managing their capital. Performance measurement can be divided into financial and non-financial performance measurement. This article will discuss further about financial performance measurement using Economic Value Added (EVA) and Financial Value Added (FVA)' Economic Value Added was developed by Stern, Stewart & Company, while Financial Value Added or Financial EVA is a new indicator that was developed as an improvement of EVA. In the end of the article, there will be comparisons of advantages and disadvantages between EVA and FVA.